An analytical study of pigments in Qing Dynasty murals of Longwang Temple, Xiazhuang, Xinrong district, Datong - Haijiao , Zhang; Min , Zhang (Acta Archaeologica Lodziensia, 2023)
The frescoes of Xia Zhuang Longwang Temple in Xinrong District, Datong, were Ming Dynasty frescoes of the Qing Dynasty. To understand their pigment composition, this work used a combination of scanning electron microscopy-energy spectrometry and laser micro Raman spectroscopy to analyze the pigment samples. The results show that the murals of Xia Zhuang Longwang Temple are all inorganic pigments. The white pigment is hard gypsum, the red pigment is mainly cinnabar, the green pigment is alkaline copper chloride, the blue pigment is cobalt blue, the black and gray pigments are mainly carbon black, the pink pigment coloring component is iron red, and the yellow pigment contains coloring components cinnabar and lead. The results of the study are important for understanding the production process of folk murals and the use of pigments in the Qing Dynasty.